Diuretics in chronic kidney disease - A. I. Dyadyk; G. G. Taradin; Yu. V. Suliman; S. R. Zborovskyy; V. I. Merkuriev (SINAPS LLC, 2020)
The issues of diuretic therapy in patients with chronic kidney disease, pharmacokinetics of diuretics, the problem of diuretic resistance, the tactics of using thiazides and loop diuretics in patients with various stages of chronic kidney disease, according to the recommendations of the National Kidney Foundation Kidney Disease Outcomes Quality Initiative are discussed in the article. Particular attention is paid to the prescription of this group of drugs to patients with end stage renal disease, as well as those undergoing renal replacement therapy (hemodialysis).Diuretics play an important role in the management of patients with chronic kidney disease with the development of hypertension and an increased extracellular fluid volume. In case of impaired renal function leading place is given to loop diuretics. Their combination with thiazide diuretics can increase the diuretic effect. The results of clinical trials assessing the effectiveness of the use of diuretics during decline of residual renal function are provided. It is reported about the effect of potassium-sparing diuretics on the incidence of cardiovascular complications, the development of hyperkalemia in patients undergoing dialysis treatment. The importance of continuation of intensive study about the possibility of antagonists of mineralocorticoid receptors usage, in particular the spironolactone, eplerenone, and finerenone in order to reduce cardiovascular complications and mortality, is indicated.